PENGARUH PENGENDALIAN INTERNAL DAN GOOD CORPORATE GOVERNANCE TERHADAP PENCEGAHAN FRAUD PADA PERUSAHAAN BUMN SEKTOR JASA KEUANGAN - Bertha Elvy Napitupulu; Pinky Noer Ramadhita (Jurnal Akuntansi dan Perpajakan Jayakarta, 2022)
This study aims to determine the influence of Internal Control and Good Corporate Governance on Fraud Prevention. The variables studied were Internal Control, Good Corporate Governance, and Fraud Prevention. The type of research used was descriptive correlational quantitative research. The sampling technique used was purposive sampling technique. The population in this study was a state-owned company in the financial services sector. The total sample who filled out the research questionnaire were 38 people consisting of leaders, managers, auditors, finance and accounting, customer service, and front liners. Processing and analyzing data using multiple linear regression analysis with the help of SPSS 25 software (Statistical Product and Service Solution). The results of this study indicate that the Internal Control and Good Corporate Governance have an effect on Fraud Prevention both partially and simultaneously